2020
DOI: 10.3390/agronomy10060844
|View full text |Cite
|
Sign up to set email alerts
|

Lucerne (Medicago sativa L.) Persistence Remains Unchanged under Variable Cutting Regimes

Abstract: Lucerne (Medicago sativa L.) persistence is important for farming systems in south east Australia. Defoliation of lucerne that is too frequent (arguably more than once every six weeks) reduces yield and accelerates stand decline. Three experiments were conducted in south east Australia (Burraja, New South Wales; Rutherglen and Hamilton, Victoria) to investigate different cutting regimes on lucerne persistence. At Burraja lucerne was cut 16 (lax) or 33 (severe) times over three years at different plant densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Lucerne ( Medicago sativa L.) plant density has an important role in affecting its forage yield and stand persistence over successive years. This was shown in several studies that documented the relationship between plant density, yield, yield‐component traits or stand persistence (Burnett et al., 2020; Min et al., 2000; Stanisavljević et al., 2012). For lucerne producers, adjusting the sowing rate is usually the main method for manipulating the eventual plant density in the field, and its effect has been studied in several regions and over many decades (Berti & Samarappuli, 2018; Lamb et al., 2003; Thompson & Stout, 1996).…”
Section: Introductionmentioning
confidence: 74%
“…Lucerne ( Medicago sativa L.) plant density has an important role in affecting its forage yield and stand persistence over successive years. This was shown in several studies that documented the relationship between plant density, yield, yield‐component traits or stand persistence (Burnett et al., 2020; Min et al., 2000; Stanisavljević et al., 2012). For lucerne producers, adjusting the sowing rate is usually the main method for manipulating the eventual plant density in the field, and its effect has been studied in several regions and over many decades (Berti & Samarappuli, 2018; Lamb et al., 2003; Thompson & Stout, 1996).…”
Section: Introductionmentioning
confidence: 74%
“…Pembleton et al (2010) showed that under a cool temperate climate, environment had a significant impact on the persistence and yield of alfalfa genotypes, with winter active genotypes having low persistence and DM yield. Breeding for grazing tolerance has been shown to be important in persistence (Sewell et al, 2011;Harvey et al, 2014;Burnett et al, 2020), but there can be a trade off in production, with winter active germplasm generally showing poor persistence (Humphries et al, 2006;Harvey et al, 2014). What is apparent, is that as the worldwide range of M. sativa expands, breeding programs to meet regional conditions will become more important (Bouton, 2012;Shi et al, 2017).…”
Section: Production and Persistencementioning
confidence: 99%
“…Legume species have great potential for production in the Mediterranean region of central Chile, because of plant survival under low rainfall conditions and the possibility to extend the growing period [42,43], but the higher CIF prices (nominal values) compared with ryegrasses and fescues could affect the adoption of these legumes by farmers (Figure S3). For instance, M. sativa is more tolerant of growth under limited water availability than a range of grasses, legumes and forage herbs species [44], and the persistence remains unchanged under different defoliation regimes [45]. This particular species has a strong Chilean seed production company that supplies an important amount of seed to farmers, masking the real use of this forage legume.…”
Section: Overview Of the Genus And Species Importedmentioning
confidence: 99%